Situation Report: Poland, 12 November 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Another Mine Disaster: More Information Available US Grants Poland 500,000,000 Dollar Credit Extensive Curbs on Alcohol Sales in Warsaw Area The Discussion about Sex in Poland Polish Catholics Publish Work by Czechoslovak Dissident